PEDIDIKAN ISLAM PADA ALUMNI HAJI DI MAJLIS TAKLIM DAN DZIKIR ASY SYAHIDIYAH WONOSOBO - Muhammad Saefullah; Robingun Suyud El Syam (LP3M KH Yazid Karimullah Institute, 2022)
The purpose of Islamic education cannot be separated from the purpose of human life in the world, namely to form a servant person who is pious and can enjoy the happiness of life in this world and the hereafter. So education for Hajj alumni must be directed there, as an effort to maintain prosperity. Through a phenomenological approach, the research resulted: Islamic education at the majlis taklim and dhikr asy syahidiyah is directed to achieve the fulfillment of human life by a continuous formation process to explore the potential of the congregation through routine and incidental religious activities. The essence of education stimulates a love for religious learning and the quality of worship so that it can develop the desire and opportunity for lifelong learning, an effort to maintain the success of the pilgrimage. This taklim assembly impressed the hearts of the congregation, they also invited their neighbors to participate so that slowly the taklim assembly grew.